Improved Hygroscopicity and Bioavailability of Solid Dispersion of Red Ginseng Extract with Silicon Dioxide - Sojeong Jin; Chul Haeng Lee; Dong Yu Lim; Jaehyeok Lee; Soo-Jin Park; Im-Sook Song; Min-Koo Choi (MDPI AG, 2021)
This study aims to develop a powder formulation for the Korean red ginseng extract (RGE) and to evaluate its in vitro and in vivo formulation characteristics. The solid dispersion of RGE was prepared with hydrophilic carriers using a freeze-drying method. After conducting the water sorption-desorption isothermogram (relative humidity between 30 and 70% RH), differential scanning calorimetry thermal behavior, dissolution test, and intestinal permeation study, a solid dispersion formulation of RGE and silicon dioxide (RGE-SiO2) was selected. RGE-SiO2 formulation increased intestinal permeability of ginsenoside Rb1 (GRb1), GRb2, GRc, and GRd by 1.6-fold in rat jejunal segments as measured by the Ussing chamber system. A 1.6- to 1.8-fold increase in plasma exposure of GRb1, GRb2, GRc, and GRd in rats was observed following oral administration of RGE-SiO2 (375 mg/kg as RGE). No significant difference was observed in the time to reach maximum concentration (Tmax) and half-life in comparison to those in RGE administered rats (375 mg/kg). In conclusion, formulating solid dispersion of RGE with amorphous SiO2, the powder formulation of RGE was successfully formulated with improved hygroscopicity, increased intestinal permeability, and enhanced oral bioavailability and is therefore suitable for processing solid formulations of RGE product.